Étendue du devoir de loyauté de l’agent en l’absence de clause restrictive - Faribault, Geneviève (Assurances)

(untitled) (HEC Montréal, 1996)
After having briefly reviewed the main elements of the notion of disloyal competition, as applicable to insurance agents, Me Faribault defines the various criteria of the loyalty obligation that insurance intermediaries must respect when they leave an insurance company to join another. The author also looks at who owns the clientele, the agent or the company? After answering this question, our collaborator explains the recourses available to an insurance company when a former agents begins to systematically replace its contracts. Lastly, the study provides a list of acts that can render questionable the good faith of the insurance company or market intermediary.